Kinetics and mechanism of gas-phase thermolysis using headspace-gas chromatographic analysis - Cafferata, Lázaro F. R. (2001)
Headspace gas chromatography is employed in order to study the thermal decomposition reaction of gaseous di-tert-butyl peroxide (DTBP) in the 130°C to 160°C temperature range and in the presence of n-hexane as the internal standard and nitrogen as the carrier gas. The reaction exclusively yields acetone and ethane as products. First-order kinetics are observed, including when the surface-to-volume ratio (S/V) of the Pyrex 20-mL vial employed as the reactor is increased by packing it with silanized glass wool. However, a small increase in the rate constant values is observed at each temperature, which supports a heterogeneous surface process in DTBP decomposition. The rate constant's dependence on the homogeneous unimolecular decomposition reaction corresponds to the O-O bond rupture of the DTBP molecule in a stepwise three-stage mechanism. Thus, the relevant question of the participation of a surface catalytic effect in the DTBP gas-phase thermolysis can easily be assessed through the procedure described in this work. In general, this is advantageous for the rapid investigation of the reaction kinetics of volatile compounds at different temperatures.